An intracranial yolk sac tumor with initial symptom of hemorrhage in the basal ganglia: a case report - Liu, Qiang; Du, Xuecui; Wang, Yunyan; Hou, Ruihua; Chen, Yuqing; Chen, Teng (Frontiers in Oncology, 2024)
We report a case and follow-up of an adult male with intracranial yolk sac tumor (YST). Initially, the patient presented with abnormal high signals in the right basal ganglia on MRI, misdiagnosed as a cavernous hemangioma. However, within 2 years, the condition rapidly progressed into a large, hypervascular solid neoplasm leading to a basal ganglia hemorrhage. Comprehensive evaluation of clinical symptoms, imaging, surgical findings, serology, histopathology, and genetic analysis confirmed the diagnosis of a yolk sac tumor. The patient underwent prompt surgical resection followed by radiotherapy and chemotherapy. Six months post-treatment, his condition remains stable, with no recurrence. Notably, early MRI revealed Wallerian degeneration in the brainstem suggesting that benign-appearing basal ganglia lesions may sometimes result from malignant infiltration by germ cell tumors or other cancers. To prevent misdiagnosis and ensure timely treatment, a stereotactic biopsy is recommended. We hope this case provides a valuable reference for diagnosing and treating YSTs and contributes to ongoing research aimed at improving patient survival.